Different economic and policy perspectives in micro population for sustainable development: A study of the Haor livelihood in Bangladesh - Rabby, Talukder Golam; Alam, Gazi Mahabubul; K. Mishra, Pradip; Hoque, Kazi Enamul; Nair, Sulochana (Academic Journals, 2011)
Criteria of development approaches and their schemata have evolved out of historical social practices. Interpretation of social events is guided and constrained by the prevailing rationality which itself reflects the dominant constellation of power. With the course of change of time and modernization, a number of development approaches have taken place especially in the context of developing nations. However, the discourse of the development of a less number of populations who are having geographically disadvantaged, unskilled and physically challenged positions is always seen as critical, since it requires high investment from public subsidy but provides less public and private returns. Factually, without the development of these populations, state mission will be missed out. Considering this is an issue for research in the area of public policy and development studies, this study was conducted in Bangladesh with a scientific adoption of both quantitative and qualitative methods, intending to discover an approach that helps the particular group to develop without hampering the return to the investment made by the state. Although, this study was conducted in Bangladesh, the development approach discovered can be used to many other developing country contexts.